Tailoring Microalgae for Efficient Biofuel Production - Sharma, Prabin Kumar; Saharia, Manalisha; Srivstava, Richa; Kumar, Sanjeev; Sahoo, Lingaraj (Frontiers in Marine Science, 2018)
Depleting fossil fuel, soaring price, growing demand and global climate change concerns have driven research for finding alternative source of sustainable fuel. Microalgae have emerged as a potential feedstock for biofuel production as many strains accumulate high amounts of lipid, with faster biomass growth and higher photosynthetic yield than that of their land plant counterparts, without needing agricultural land or ecological landscapes, and offering opportunities for mitigating global climate change allowing waste water treatment and CO2 sequestration. Despite these benefits, microalgae pose many challenges, including low lipid yield under limiting growth conditions and slower growth in high lipid content strains. Biotechnological interventions can make major advances in strain improvement for commercial scale production of biofuel. We discuss various strategies including efficient transformation toolbox, and to increase lipid accumulation and its quality through regulation of key enzymes involved in lipid production, blocking the competing pathways, pyramiding genes, enabling high cell biomass under nutrient deprived conditions and other environmental stresses, and controlling the upstream regulators of targets, the transcription factors and microRNAs. We highlight the opportunities emerging from the current progress in application of genome editing in microalgae for accelerating strain improvement program.